Successful intrabdominal preterm pregnancy: A case report: Embarazo pretérmino intrabdominal exitoso: Reporte de caso - Abud-Flores, Saida Anyul (2024)
Introduction: Ectopic pregnancy is any gestation in which the implantation site of the fertilized egg is located outside the endometrial cavity. Abdominal ectopic pregnancy represents 1.4% of these. Case report: 28-year-old patient with two previous cesarean sections; bilateral tubal obstruction during the last operation. The patient was admitted to the hospital with blood pressure of 180/130 mm Hg that did not respond to medical treatment and not progression to labor so it was decided to interrupt the pregnancy by cesarean section. During surgery, a small uterus with extrauterine pregnancy was observed adhered to the serosa of the cecum, ascending colon, and appendix. A live preterm female product was obtained; the mother had a favorable evolution and no postoperative complications. Conclusion: Ectopic pregnancies are rera. An adequate prenatal control by well trained personnel is essential for an accurate diagnosis. The mother and the newborn did not present any complication. It is very important to have and accurate an opportune diagnosis so trained personnel can offer an adequate management.